APPLICATION OF THE PREPARATION OF FINANCIAL REPORTING STANDARD ACCOUNTING FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK EMKM) IN CLEAN WASH LAUNDRY BUSINESSES IN PONTIANAK - Miranda, Nabilla; Hijriah, Amanah; Yunita, Khristina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Despite the critical role MSMEs play in Indonesia's economic development, many do not comply with the Financial Accounting Standards for Micro, Small, and Medium Enterprises when they are putting together their financial statements. This study aims to present the correct format for Clean Wash Laundry's financial reports according to SAK EMKM and to identify the challenges faced during this process. The research collected primary data through interviews and documentation studies using a qualitative descriptive method. The results show that Clean Wash Laundry only records daily income and expenses and does not adhere to SAK EMKM, mainly due to unfamiliarity with these standards.